Utilization of Avocado (Persea americana) as a Local Food Resource in Aikmel Utara Village for Stunting Prevention - suzana hasmi (Postgraduate Program, University of Mataram, 2024)
Stunting is a growth and development disorder in children caused by chronic malnutrition and repeated infections, characterized by a height or length below the standard. In recurring conditions (throughout the life cycle), food that is nutritionally deficient in early life (the first 1000 days) carries a risk of non-communicable diseases in adulthood. In Aikmel Utara Village, 74 children were identified as experiencing stunting, with 9 children categorized as very short and 65 children categorized as short. This study aims to analyze the potential use of avocado (Persea americana) as a local food to prevent stunting in Aikmel Utara Village. The method used is qualitative descriptive through interviews, observations, documentation study, and scientific references.Research results show that avocados contain healthy fats, vitamin C, folic acid, potassium, as well as enough energy to support child growth and the health of pregnant women. Avocados can be processed into various products such as juice, smoothies, avocado seed flour, pudding, and so on. This study concludes that avocados can be utilized as a local food that supports the stunting reduction program in North Aikmel Village through nutrition education and food processing innovation.